2013
DOI: 10.1007/s00264-012-1764-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of a computerised navigation technique to assist arthroscopic anterior cruciate ligament reconstruction

Abstract: Purpose Based on biomechanical cadaver studies, anatomical double-bundle reconstruction of the anterior cruciate ligament (ACL) was introduced to achieve better stability in the knee, particularly in respect of rotatory loads. Previously, the success of ACL reconstruction was believed to be mainly dependent on correct positioning of the graft, irrespective of the number of bundles for which computer-assisted surgery was developed to avoid malpositioning of the tunnel. The aim of this study was to compare rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…For this reason, a novel surgical procedure, the STDB reconstruction, is developed to provide an alternative treatment method for restoring the normal anatomic structures and biomechanical properties [24]. It is to reconstruct two bundles (AM and PL) of different functions by separating the two bundles of ligament in the tunnel, which is characterized by simple operation, ability of simulating the DTDB anatomic property and excellent anterioposterior and rotation stability, shortening surgical time and decreasing di culty and risk of DBDT pattern [25,26]. Gadikota et al measured biomechanical properties of the cadaveric knee specimen in the action of forward-load and found that compared to the STSB reconstruction, the STDB was more equal to normal ACL with regard to biomechanical properties [21].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a novel surgical procedure, the STDB reconstruction, is developed to provide an alternative treatment method for restoring the normal anatomic structures and biomechanical properties [24]. It is to reconstruct two bundles (AM and PL) of different functions by separating the two bundles of ligament in the tunnel, which is characterized by simple operation, ability of simulating the DTDB anatomic property and excellent anterioposterior and rotation stability, shortening surgical time and decreasing di culty and risk of DBDT pattern [25,26]. Gadikota et al measured biomechanical properties of the cadaveric knee specimen in the action of forward-load and found that compared to the STSB reconstruction, the STDB was more equal to normal ACL with regard to biomechanical properties [21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, computer-aided technique could better determine the locations for injured ACL. [23][24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
“…Para mejorar esta situación, se han diseñado diversos dispositivos asistentes que incrementan la orientación espacial de los cirujanos durante las intervenciones ortopédicas y son conocidos como sistemas de Cirugía Ortopédica Asistida por Computador o Computer Assisted Orthopaedic Surgery, CAOS en inglés (JOST et al, 2014). Algunos de estos sistemas son: Orthopilot ACL (OCHI et al, 2016) de la empresa alemana B-Braun, siendo uno de los más usados en instituciones médicas alrededor del mundo (KLOS, 2014); el VectorVision ACL de BrainLab (ZHU et al, 2013) y Surgetics de la compañía Praxim Medvision (KOH et al, 2014). Estos sistemas han demostrado ser un apoyo importante para los cirujanos en labores de precisión como la perforación de túneles ((KOH et al 2014, PETERSON et al 2015, disminuyendo el porcentaje de cirugías de revisión a largo plazo (GORADIA, 2014), igualmente ayudan a mejorar la precisión de la orientación anatómica del túnel y la posición durante la cirugía reconstructiva del LCA (ZAFFAGNINI et al, 2016).…”
Section: Introductionunclassified
“…Estos sistemas han demostrado ser un apoyo importante para los cirujanos en labores de precisión como la perforación de túneles ((KOH et al 2014, PETERSON et al 2015, disminuyendo el porcentaje de cirugías de revisión a largo plazo (GORADIA, 2014), igualmente ayudan a mejorar la precisión de la orientación anatómica del túnel y la posición durante la cirugía reconstructiva del LCA (ZAFFAGNINI et al, 2016). De igual manera, se han posicionado ampliamente en el entrenamiento de cirujanos ortopedistas, permitiéndoles reducir su curva de aprendizaje (ANTHONY et al 2013, ZHU et al 2013. A pesar de esto, estudios evidencian, que el costo de implementación de estos sistemas es elevado, lo que ha evitado su propagación en la práctica quirúrgica (MARGIER et al, 2015), convirtiéndose de esta manera en una barrera para la apropiación de ese tipo de tecnologías.…”
Section: Introductionunclassified